Digital Innovation and Financial Governance as Catalysts for Investor Trust in Start-Up in Yogyakarta - Loso Judijanto; Septiana Na'afi; Siti Zuhroh (Westscience Press, 2024)
Investor trust is a cornerstone for the growth and sustainability of start-ups, particularly in competitive entrepreneurial hubs like Yogyakarta. This study investigates the influence of digital innovation and financial governance on investor trust in start-ups. Using a quantitative approach, data were collected from 50 start-ups through a structured questionnaire measured on a Likert scale of 1-5. Data analysis with SPSS version 26 reveals that both digital innovation and financial governance significantly and positively influence investor trust. Moreover, the combined effect of these factors accounts for 62% of the variance in investor trust, underscoring their complementary roles. These findings highlight the importance of leveraging technological advancements and robust financial practices to foster investor confidence. The study contributes to the existing literature by providing empirical evidence of these relationships and offers practical implications for start-up founders and policymakers.